Biodegradable laminate, method for producing the same, and molded body
Patent Information
- Application Number
- CN202380019905.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-08
- Filing Date
- 2023-01-31
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-01-31
AI Technical Summary
[0011]对于专利文献1所记载的层叠体而言,尽管存在纸基材与生物降解性树脂层间的层压强度得到改善的倾向,但存在树脂层的机械强度低、弯曲加工时产生裂纹、热封性低、不足以进行杯成型等的课题
[0018]根据本发明,可以提供层叠有纸基材层和包含聚(3-羟基烷酸酯)类树脂的热塑性树脂层的生物降解性层叠体及其制造方法,所述生物降解性层叠体在纸基材层与热塑性树脂层之间具有充分的粘接强度,且具有能够耐受弯曲加工的机械强度和能够耐受杯成型等的高热封性。
Smart Images

Figure CN118647507B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a biodegradable laminate having a paper substrate layer and a thermoplastic resin layer comprising a poly(3-hydroxyalkanoate) resin, a method for manufacturing the same, and a molded article thereof. Background Technology
[0002] In recent years, environmental problems caused by waste plastics have attracted much attention. Among them, marine pollution caused by waste plastics is very serious, and there is a growing expectation for the widespread use of biodegradable resins that can decompose in the natural environment.
[0003] Various resins are known as biodegradable resins, among which poly(3-hydroxyalkanoate) resins (hereinafter also referred to as "P3HA resins") are thermoplastic polyesters produced and accumulated within the cells of many microbial species as energy storage substances. Because they are biodegradable not only in soil but also in seawater, they have attracted attention as raw materials for solving the aforementioned problems. Composite materials made by integrating P3HA resins with paper substrates have particularly high social attention due to their potential for application in environmentally friendly food contact containers.
[0004] Methods for integrating P3HA-type resins with paper substrates include extrusion lamination and coating with aqueous slurry. Since it is difficult to obtain sufficient mechanical strength of the resin layer in the coating method, extrusion lamination is preferred.
[0005] However, when using extrusion lamination, P3HA resins with high mechanical strength typically tend to have high molecular weights and consequently high melt viscosity. Because the penetration of high melt viscosity P3HA resins into paper is significantly impaired, it is difficult to laminate such P3HA resins onto paper with sufficient strength. As a result, the resin layer may peel off from the paper during the manufacturing process of cups and other molded products, causing leakage when filling with contents.
[0006] Patent Document 1 discloses a method for improving the lamination strength of a paper substrate and a biodegradable resin layer: a dispersion or emulsion containing 50% by weight or more polycaprolactone is applied at a concentration of 10 g / m³. 2 After the unit area weight (dry weight of the layer) is coated onto a paper substrate and dried, a biodegradable resin with 3-hydroxybutyric acid / 3-hydroxyvalerate copolymer as the main component, which is a type of P3HA resin, is extruded and laminated to produce a laminate.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent Application Publication No. 6-293113 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] Regarding the laminate described in Patent Document 1, although there is a tendency to improve the lamination strength between the paper substrate and the biodegradable resin layer, there are problems such as low mechanical strength of the resin layer, cracking during bending processing, low heat sealability, and inadequacy for cup forming.
[0012] In addition, since polycaprolactone, which has an extremely low melting point of 60°C, is used as an essential component, there is a risk of reduced lamination strength and lamination peeling, for example, when filling hot beverages into cup molds.
[0013] In view of the above, the object of the present invention is to provide a biodegradable laminate composed of a paper substrate layer and a thermoplastic resin layer comprising a poly(3-hydroxyalkanoate) resin, and a method thereof for manufacturing the same, wherein the biodegradable laminate has good lamination strength, sufficient mechanical strength, and high heat-sealing properties that can withstand cup forming and the like.
[0014] Methods for solving problems
[0015] This invention relates to a biodegradable laminate comprising, in sequence: a paper substrate (A) layer, a first thermoplastic resin (B) layer with poly(3-hydroxyalkanoate) resin as the main component, and a second thermoplastic resin (C) layer with poly(3-hydroxyalkanoate) resin as the main component.
[0016] The first thermoplastic resin (B) contains a poly(3-hydroxyalkanoate) resin with a weight-average molecular weight of 100,000 or more and less than 350,000, and the second thermoplastic resin (C) contains a poly(3-hydroxyalkanoate) resin with a weight-average molecular weight of 450,000 or more and less than 700,000.
[0017] The effects of the invention
[0018] According to the present invention, a biodegradable laminate comprising a paper substrate layer and a thermoplastic resin layer comprising a poly(3-hydroxyalkanoate) resin and a method thereof can be provided, wherein the biodegradable laminate has sufficient adhesive strength between the paper substrate layer and the thermoplastic resin layer, and has mechanical strength capable of withstanding bending processes and high heat-sealing properties capable of withstanding cup forming and the like.
[0019] According to the present invention, since the thermoplastic resin layer is composed of two layers with poly(3-hydroxyalkanoate) resin as the main component with a high melting point, it is possible to obtain the advantage that the lamination strength of the biodegradable laminate is not easily reduced when exposed to high temperature, such as when filling hot beverages in a cup mold.
[0020] When using the biodegradable laminate of the present invention, the production efficiency and quality of the molded articles can be improved. Attached Figure Description
[0021] Figure 1 This is a schematic cross-sectional view of the biodegradable laminate of the first embodiment of the present invention.
[0022] Figure 2 This is a schematic cross-sectional view of the biodegradable laminate of the second embodiment of the present invention.
[0023] Symbol Explanation
[0024] 1. Biodegradable laminates
[0025] 2. Paper substrate (A) layer
[0026] 3. First thermoplastic resin (B) layer
[0027] 4. Second thermoplastic resin (C) layer
[0028] 5. Adhesive resin (D) layer Detailed Implementation
[0029] The embodiments of the present invention will be described below, but the present invention is not limited to the following embodiments.
[0030] [Biodegradable laminates]
[0031] The biodegradable laminate of the first embodiment of the present invention comprises, in sequence: a paper substrate (A) layer, a first thermoplastic resin (B) layer with poly(3-hydroxyalkanoate) resin as the main component, and a second thermoplastic resin (C) layer with poly(3-hydroxyalkanoate) resin as the main component. Figure 1 The layer structure of this method is shown in the diagram. Figure 1 In the text, symbol 1 refers to the biodegradable laminate, symbol 2 refers to the paper substrate (A) layer, symbol 3 refers to the first thermoplastic resin (B) layer, and symbol 4 refers to the second thermoplastic resin (C) layer.
[0032] Furthermore, from the viewpoint of improving heat-sealing properties during cup forming, the biodegradable laminate of the second aspect of the present invention may have an adhesive resin (D) layer laminated on the back side of the paper substrate (A) layer on which the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer are laminated. Figure 2 The layer structure of this method is shown in the diagram. Figure 2 In the middle, symbols 1 to 4 and Figure 1 Symbols 1 to 4 are the same, and symbol 5 refers to the adhesive resin (D) layer.
[0033] In either the first or second method, the first thermoplastic resin (B) layer can be directly laminated onto the paper substrate (A) layer. Without compromising adhesion, other resin layers can be further included as intermediate layers between the (A) and (B) layers. Additionally, for purposes such as imparting water resistance and gloss, other resin layers can be further laminated onto the second thermoplastic resin (C) layer.
[0034] [Paper substrate (A) layer]
[0035] As the paper substrate (A) layer, any material with paper as the main component is acceptable, with no particular limitation, but biodegradability is preferred. Examples of suitable materials include paper substrates containing, in addition to paper (with cellulose as the main component), cellulosic acid, cellulose esters, polyvinyl alcohol, polyamino acids, polyglycolic acid, pullulan, or materials formed by vapor-depositing inorganic substances such as aluminum or silica onto these paper substrates. The type of paper is not particularly limited, but examples include: paper cup base paper, kraft paper, fully chemical pulp paper, coated paper, thin-layer paper, glassine paper, and cardboard. The type of paper can be appropriately selected based on the intended use of this biodegradable laminate.
[0036] Water-resistant agents, water-repellent agents, inorganic substances, etc., can be added to the paper as needed. Surface treatments such as oxygen barrier coating and water vapor barrier coating can also be applied. In addition, surface treatments such as corona treatment, ozone treatment, plasma treatment, flame treatment, tackifying coating treatment, oxygen barrier coating, and water vapor barrier coating can be applied to the substrate layer surface. These surface treatments can be performed individually or in combination.
[0037] [First thermoplastic resin (B) layer]
[0038] The first thermoplastic resin (B) is any biodegradable resin that contains 50% or more of a poly(3-hydroxyalkanoate) resin (hereinafter also referred to as "P3HA resin") and is capable of bonding to the paper substrate (A) layer; there are no particular limitations. The content of P3HA resin in the first thermoplastic resin (B) is preferably 60% or more by weight, more preferably 70% or more by weight, further preferably 80% or more by weight, and particularly preferably 90% or more by weight.
[0039] By including a high-melting-point P3HA type resin as the main component in the first thermoplastic resin (B), it is possible to obtain advantages such as the lamination strength of the biodegradable laminate not easily decreasing when exposed to high temperatures, for example, when filling a cup mold with a hot beverage.
[0040] P3HA resins are biodegradable aliphatic polyesters (polyesters without aromatic rings) containing repeating 3-hydroxyalkanoate units represented by the general formula: [-CHR-CH2-CO-O-] (where R is a carbonyl ester compound with C646-C ... nH 2n+1 The polyhydroxyalkanoate (where n is an integer of 1 or more and 15 or less, representing an alkyl group). Preferably, it contains 50 mol% or more of the repeating unit relative to all monomer repeating units (100 mol%), more preferably 70 mol% or more.
[0041] Among P3HA resins, poly(3-hydroxybutyrate) resins are preferred, especially from the viewpoints of easy availability and easy processing.
[0042] The aforementioned poly(3-hydroxybutyrate) resin (hereinafter also referred to as "P3HB resin") is a polyester resin containing 3-hydroxybutyrate as a repeating unit, and it is an aliphatic polyester resin that can be produced by microorganisms. This poly(3-hydroxybutyrate) resin can be a poly(3-hydroxybutyrate) with only 3-hydroxybutyrate as a repeating unit, or it can be a copolymer of 3-hydroxybutyrate and other hydroxyalkyl esters. Furthermore, the aforementioned poly(3-hydroxybutyrate) resin can be a mixture of homopolymer and one or more copolymers, or it can be a mixture of two or more copolymers.
[0043] Specific examples of the aforementioned poly(3-hydroxybutyrate) resins include: poly(3-hydroxybutyrate) (hereinafter also referred to as "PHB"), poly(3-hydroxybutyrate-copolymer-3-hydroxyhexanoate) (hereinafter also referred to as "P3HB3HH"), poly(3-hydroxybutyrate-copolymer-3-hydroxyvalerate), poly(3-hydroxybutyrate-copolymer-4-hydroxybutyrate), poly(3-hydroxybutyrate-copolymer-3-hydroxyoctanoate), poly(3-hydroxybutyrate-copolymer-3-hydroxyoctadecanoate), poly(3-hydroxybutyrate-copolymer-3-hydroxydecanoate), and poly(3-hydroxybutyrate-copolymer-3-hydroxyvalerate-copolymer-3-hydroxyhexanoate). Among these, poly(3-hydroxybutyrate), poly(3-hydroxybutyrate-copolymer-3-hydroxyhexanoate), poly(3-hydroxybutyrate-copolymer-3-hydroxyvalerate), and poly(3-hydroxybutyrate-copolymer-4-hydroxybutyrate) are preferred from the perspective of ease of industrial production.
[0044] By changing the composition ratio of repeating units, the melting point, crystallinity, Young's modulus, heat resistance, and other physical properties can be altered, thus imparting properties between polypropylene and polyethylene. Furthermore, it is easy to produce industrially and is a useful plastic in terms of physical properties; from this perspective, it is particularly preferred. Among poly(3-hydroxybutyrate) resins that readily undergo thermal decomposition at temperatures above 180°C, P3HB3HH is preferred from the viewpoint of lowering the melting point and enabling low-temperature molding.
[0045] The average content ratio of each constituent monomer in P3HB3HH is preferably 3HB / 3HH = 97-80 / 3-20 (mol% / mol%), more preferably 3HB / 3HH = 94-82 / 6-18 (mol% / mol%). When the average content ratio of 3HH in P3HB3HH is 3 mol% or more, good adhesion can be obtained in the heat sealing test described later. In addition, the crystallization rate of P3HB3HH with an average content ratio of 3HH of 20 mol% or less does not become too slow, making it easier to manufacture. It should be noted that the average content ratio of each component in P3HB3HHH can be determined by methods known to those skilled in the art, such as the method described in paragraph
[0047] of International Publication No. 2013 / 147139, or by NMR determination. The average content ratio refers to the molar ratio of 3HB to 3HH contained in P3HB3HH. In the case that P3HB3HH is a mixture containing at least two types of P3HB3HH, or a mixture containing at least one type of P3HB3HH and PHB, it refers to the molar ratio of each monomer contained in the mixture as a whole.
[0046] As described above, P3HB3HH with an average content of 3 to 20 mol% is particularly preferably composed of at least two P3HB3HHs with different contents of each other constituting the monomers, and is also preferably composed of at least one P3HB3HH and PHB.
[0047] The specific manufacturing method of P3HB3HH is described, for example, in International Publication No. 2010 / 013483.
[0048] In addition, commercially available products as P3HB3HH include Kaneka Corporation's "KANEKA Biodegradable Polymer Green Planet" (registered trademark).
[0049] The first thermoplastic resin (B) may consist solely of P3HA resins, or it may include biodegradable resins other than P3HA resins, such as polycaprolactone, polybutylene adipate, polybutylene succinate, polylactic acid, polybutylene adipate, polybutylene azelaate, etc.
[0050] According to a preferred embodiment, the first thermoplastic resin (B) may contain 50% by weight or more of P3HB3HH. The proportion of P3HB3HH in the first thermoplastic resin (B) is preferably 60% by weight or more, more preferably 70% by weight or more, further preferably 80% by weight or more, and particularly preferably 90% by weight or more. In this embodiment, the first thermoplastic resin (B) may consist solely of P3HB3HH, or may contain P3HA-type resins other than P3HB3HH, and / or biodegradable resins other than the aforementioned P3HA-type resins as thermoplastic resins other than P3HB3HH.
[0051] From the viewpoint of achieving good adhesion or lamination strength to the paper substrate (A) layer, the weight-average molecular weight (hereinafter sometimes referred to as Mw) of the P3HA-type resin included in the first thermoplastic resin (B) is preferably 100,000 or more and less than 350,000, more preferably 150,000 or more and less than 300,000, and even more preferably 200,000 or more and less than 250,000. Furthermore, the lower limit can be 250,000 or more, or 300,000 or more. When the weight-average molecular weight is less than 100,000, the amount of leaching during heating may increase, sometimes making it unsuitable for use as a food container, and extrusion processing may also significantly increase decomposition products, potentially reducing the lamination strength with the paper substrate (A) layer. Conversely, if the weight-average molecular weight is 350,000 or more, the melt viscosity of the resin increases, thus sometimes reducing the adhesion or lamination strength to the paper substrate (A) layer.
[0052] It should be noted that, in this application, the weight-average molecular weight of P3HA resin can be determined using a gel permeation chromatography (GPC) instrument (Shodex GPC-101 manufactured by Showa Denko Corporation), with polystyrene gel (Shodex K-804 manufactured by Showa Denko Corporation) in the column and chloroform as the mobile phase, in the form of molecular weight after polystyrene conversion.
[0053] In one embodiment of the present invention, a variety of P3HA resins with different weight-average molecular weights may be mixed in the first thermoplastic resin (B).
[0054] When multiple P3HA resins are used in combination, the weight-average molecular weight of the P3HA resins contained in the first thermoplastic resin (B) refers to the total weight-average molecular weight of the multiple P3HA resins contained in the first thermoplastic resin (B).
[0055] To the extent that it does not impair the effects of the invention, the first thermoplastic resin (B) layer may contain one or more other additives commonly added to resin materials, such as inorganic fillers, colorants like pigments and dyes, odor absorbers like activated carbon and zeolite, fragrances like vanillin and dextrin, plasticizers, antioxidants, weather-resistant modifiers, ultraviolet absorbers, nucleating agents, lubricants, release agents, water-repellent agents, antibacterial agents, slip modifiers, and other minor additives. These are arbitrary components, and the first thermoplastic resin (B) layer may not contain these components. As arbitrary components, from the viewpoint of improving peelability from the pressing surface of cooling rollers, etc., during lamination of the first thermoplastic resin (B), lubricants and / or inorganic fillers are preferred.
[0056] Examples of such lubricants include: saturated or unsaturated fatty acid amides such as lauryl amide, myristyl amide, palmitamide, stearamide, behenyl amide, oleamide, and erucamide; aliphatic amide compounds such as methylene distearate amide and methylene distearate amide; and pentaerythritol.
[0057] The amount of lubricant in the first thermoplastic resin (B) layer is preferably 0.1 to 2 parts by weight, more preferably 0.2 to 1 part by weight, relative to 100 parts by weight of the first thermoplastic resin (B). By setting the amount to 0.1 parts by weight or more, the improved peelability due to the lubricant can be obtained. Conversely, if the amount exceeds 2 parts by weight, the lubricant will leak and adhere to the pressing surface of the cooling roller, etc., during pressing, which may sometimes make it difficult to perform continuous processing for a long time.
[0058] Examples of inorganic fillers include talc, calcium carbonate, mica, silica, clay, kaolin, titanium dioxide, alumina, and zeolite. The average particle size of the inorganic filler is preferably 0.5 μm or more.
[0059] The amount of inorganic filler in the first thermoplastic resin (B) layer is preferably 0.5 to 5 parts by weight relative to 100 parts by weight of the first thermoplastic resin (B), more preferably 1 to 3 parts by weight. By setting the amount to 0.5 parts by weight or more, the improved peelability due to the inorganic filler can be obtained. Conversely, when the amount exceeds 5 parts by weight, cracks may easily form in the first thermoplastic resin (B) layer.
[0060] The average thickness (t) of the first thermoplastic resin (B) layer B Preferably, the micrometer size is greater than 5μm and less than 30μm. B When the thickness is 5μm or greater, the adhesion to the paper substrate (A) becomes better, and peeling of the thermoplastic resin (B) layer is more easily prevented. BWhen the thickness is less than 30 μm, it is easier to prevent cracks from affecting the second thermoplastic resin (C) layer, even if cracks occur in the first thermoplastic resin (B) layer. B The lower limit is more preferably 10 μm or more, and even more preferably 15 μm or more. In addition, the upper limit can be 25 μm or less.
[0061] [Second thermoplastic resin (C) layer]
[0062] Regarding the details of the resin composition and other components constituting the second thermoplastic resin (C) layer, except for the weight-average molecular weight of the P3HA type resin described below, the details are the same as those constituting the first thermoplastic resin (B) layer. However, the types and contents of the components constituting the first thermoplastic resin (B) layer may differ from those constituting the second thermoplastic resin (C) layer within the scope of this application's disclosure.
[0063] Regarding the weight-average molecular weight of the P3HA-type resin included in the second thermoplastic resin (C), from the viewpoint of ensuring mechanical strength to withstand bending processes and high heat-sealing properties to withstand cup molding, it is preferably 450,000 or more and less than 700,000, more preferably 500,000 or more and less than 650,000, and even more preferably 550,000 or more and less than 600,000. When the weight-average molecular weight is less than 450,000, cracks may form in the resin layer during bending processes, posing a risk of leakage of moisture and oil from the contents. Furthermore, if it is 700,000 or more, the melt viscosity of the resin becomes too high, making melt extrusion processing difficult and sometimes resulting in poor heat-sealing properties during cup molding.
[0064] In one embodiment of the present invention, a variety of P3HA resins with different weight-average molecular weights may be mixed in the second thermoplastic resin (C).
[0065] When multiple P3HA resins are used in combination, the weight-average molecular weight of the P3HA resins contained in the second thermoplastic resin (C) refers to the overall weight-average molecular weight of the multiple P3HA resins contained in the second thermoplastic resin (B).
[0066] The average thickness (t) of the second thermoplastic resin (C) layer C Preferably, the micrometer size is 10 μm or larger. C When the thickness is 10 μm or greater, it can suppress cracks in the resin layer that may occur during bending processes such as cup molding. C More preferably, it is 20 μm or more; even more preferably, it is 30 μm or more; and particularly preferably, it is 40 μm or more. Additionally, t C The upper limit can be below 90μm or below 80μm.
[0067] The average thickness (t) of the first thermoplastic resin (B) layer B The average thickness (t) of the second thermoplastic resin (C) layer and the average thickness of the second thermoplastic resin (C) layer C The sum of (t) B +t C Preferably, it should be less than 100 μm. B +t C When the thickness is less than 100 μm, the paper substrate (A) is less prone to warping, which can improve the formability of molded objects such as cups.
[0068] In addition, t C Divide by t B The obtained value (t) C / t B (Preferably 2 or more.) C / t B When the value is 2 or higher, cracks generated in the first thermoplastic resin (B) layer during cup molding, such as bending, are less likely to affect the second thermoplastic resin (C) layer, thus further improving the overall mechanical strength of the resin layers. C / t B A value of 2.2 or higher is preferred. C / t B The upper limit can be 4 or less.
[0069] The average thickness of the first thermoplastic resin (B) layer and the average thickness of the second thermoplastic resin (C) layer more preferably satisfy all of the following (a) to (d).
[0070] (a) The average thickness (t) of the first thermoplastic resin (B) layer mentioned above B ) greater than 5μm
[0071] (b) The average thickness (t) of the second thermoplastic resin (C) layer mentioned above. C ) greater than 10μm
[0072] (c)t B With t C The sum is less than 100μm
[0073] (d) Using t C Divide by t B The obtained value is 2 or higher.
[0074] [Adhesive Resin (D) Layer]
[0075] As the adhesive resin (D), any adhesive resin commonly used in the coated paper or resin film industry is acceptable, without particular limitation. Preferably, it includes a paper substrate and at least one resin with high affinity for P3HA-type resins. Examples of such resins are not particularly limited, including, but can be, ester resins, acrylic resins, methacrylic resins, vinyl chloride resins, styrene-acrylic resins, styrene-butadiene resins, styrene-isoprene resins, polycarbonate resins, urea resins, melamine resins, epoxy resins, phenolic resins, urethane resins, diallyl phthalate resins, imide resins, etc. One of these resins can be used, or two or more types of resins can be mixed in any proportion as needed.
[0076] The adhesive resin (D) can be a water-soluble adhesive resin or an adhesive resin soluble in organic solvents.
[0077] From the perspective of achieving a balance between heat-sealing properties during cup molding and drying characteristics during production, the unit area weight of the adhesive resin (D) layer is preferably 0.1 g / m². 2 Above and below 5.0 g / m 2 More preferably 0.3 g / m 2 Above and below 3.0 g / m 2 Further preferred is 0.5g / m 2 Above and below 1.0 g / m 2 The weight per unit area is 0.1 g / m². 2 At the above levels, the improved heat-sealing properties during cup molding can be fully achieved. The unit area weight is less than 5.0 g / m². 2 When drying, the heat required is reduced, thus reducing the burden on the equipment. For example, it can prevent sticking of the original roll due to poor drying.
[0078] [Manufacturing method of laminated body]
[0079] The manufacturing method of the first embodiment is simply a method of sequentially laminating a first thermoplastic resin (B) layer with P3HA-type resin as the main component and a second thermoplastic resin (C) layer with P3HA-type resin as the main component on one side of a paper substrate (A) layer, without any particular limitation.
[0080] As a method for laminating the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer, from the viewpoints of adhesion, manufacturability, and resistance to thermal degradation, it is preferable to form the layer by extrusion lamination, co-extrusion lamination, or hot lamination.
[0081] Specifically, examples include: extrusion lamination or co-extrusion lamination, in which molten resin material containing a first thermoplastic resin (B) and / or a second thermoplastic resin (C) is extruded from a T-die in film form, cooled by a cooling roller, and pressed onto a separately supplied paper substrate (A) or a laminate containing a paper substrate (A) layer; and hot lamination, in which a pre-made film containing a first thermoplastic resin (B) or a second thermoplastic resin (C) is heated and pressed onto a paper substrate (A) or a laminate containing a paper substrate (A) layer. The pressing surface only needs to be able to press the resin material containing the first thermoplastic resin (B) and / or the second thermoplastic resin (C) onto the paper substrate (A) or the laminate containing a paper substrate (A) layer; examples include a plate-like surface, the surface of a roller, etc.
[0082] From the viewpoint of improving the lamination strength between the paper substrate (A) layer and the first thermoplastic resin (B) layer, or between the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer, it is preferable that at least one of the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer is formed by extrusion lamination. From the viewpoint of further improving the lamination strength between the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer, it is preferable to simultaneously form the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer on the paper substrate (A) layer by co-extrusion lamination. In addition, from the viewpoint of easily producing a biodegradable laminate containing any configuration by performing melt extrusion processing and bonding processing in other processes, it is also preferable that at least one of the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer is formed by hot lamination. It should be noted that, for purposes such as improving the adhesion between the paper substrate (A) with the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer, corona treatment may also be applied to the surface of the extruded laminate or the hot laminate.
[0083] From the viewpoint of improving the heat-sealing properties during cup forming, the manufacturing method of the second aspect of this embodiment preferably further includes a step of laminating an adhesive resin (D) layer on the back side of the paper substrate (A) layer. In this case, the adhesive resin (D) layer can be laminated on the back side of the paper substrate (A) layer after the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer have been laminated on the paper substrate (A) layer; alternatively, the adhesive resin (D) layer can be laminated on one side of the paper substrate (A) layer beforehand, followed by laminating the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer on the other side of the paper substrate (A) layer.
[0084] The adhesive resin (D) layer can be formed by coating the surface of the paper substrate (A) layer with an aqueous dispersion or an organic solvent solution of the adhesive resin (D) and then drying it, i.e., a known coating method. Alternatively, if the adhesive resin (D) is a water-insoluble resin, other additives may be added to improve dispersibility and coatability in water. When coating with an aqueous dispersion, the concentration of the solid component of the adhesive resin (D) is not particularly limited, but to keep the heat required for drying low, it is preferably 30% by weight or more, more preferably 40% by weight or more, and even more preferably 50% by weight or more. Furthermore, since the settling of the dispersed resin can sometimes adversely affect coatability, it is preferably 60% by weight or less.
[0085] The method of coating an aqueous dispersion or organic solvent solution of adhesive resin (D) onto a paper substrate (A) is not particularly limited as long as the desired coating layer can be substantially formed on the paper substrate (A). Known methods such as spray coating, dispersion coating, slot coating, air knife coating, roller coating, bar coating, corner wheel coating, doctor blade coating, screen printing, and gravure printing can be used alone or in combination. Surface treatment steps such as applying the aforementioned corona treatment to the paper substrate (A) can be performed before applying the coating solution or aqueous dispersion.
[0086] The heating treatment during drying can be carried out using known heating methods. Examples include: hot air heating, infrared heating, microwave heating, roller heating, and hot plate heating. These methods can be used individually or in combination of two or more.
[0087] [Molded body]
[0088] A molded body according to one embodiment of the present invention (hereinafter sometimes referred to as "this molded body") comprises the biodegradable laminate of the present invention (hereinafter sometimes referred to as "this laminate"). This molded body is formed from a laminate containing a P3HA-type resin with a good surface condition, and is therefore advantageous in various applications.
[0089] This molded body can be any material containing this laminate and is not particularly limited. Examples include: paper, film, sheet, tube, plate, rod, container (e.g., bottle container), bag, component, etc. From the viewpoint of countermeasures against marine pollution, this molded body is preferably a bag or bottle container.
[0090] In one embodiment of the present invention, the molded body may be the laminate itself, or it may be a molded body obtained by processing the laminate twice.
[0091] By performing two processing steps on this laminate, the molded body containing it can be preferably used as a packaging container material for various products such as shopping bags, bags of various kinds, food / snack packaging materials, cups, plates, and cartons (in other words, in various fields such as food, cosmetics, electronics, medical, and pharmaceuticals). This laminate contains a resin composition with high adhesion to the substrate and good heat resistance, therefore, it is more preferably used as a container for holding liquids, especially for beverage cups such as instant noodles, instant soup, and coffee, as well as for plates used for dishes, boxed meals, microwaveable foods, etc., to hold warm contents.
[0092] The aforementioned secondary processing can be performed using the same methods as existing resin-laminated or coated paper, i.e., using various bag-making machines, filling and packaging machines, etc. Alternatively, it can be processed using paper cup forming machines, punching machines, box-making machines, etc. In these processing machines, the bonding method for this biodegradable laminate can use known techniques, such as heat sealing, pulse sealing, ultrasonic sealing, high-frequency sealing, hot air sealing, flame sealing, etc.
[0093] The heat-sealing temperature of this laminate varies depending on the bonding method. For example, when using a heated heat-sealing tester with a sealing strip, the resin temperature is typically set to 180°C or lower, preferably 170°C or lower, and more preferably 160°C or lower. Within this range, resin leaching near the seal can be avoided, ensuring appropriate resin layer thickness and sealing strength. Furthermore, when using a heated heat-sealing tester with a sealing strip, the lower limit is typically 100°C or higher, preferably 110°C or higher, and more preferably 120°C or higher. Within this range, proper adhesion of the seal can be ensured.
[0094] The heat-sealing pressure of this laminate varies depending on the bonding method. For example, when using a heated heat-sealing tester with a sealing strip, the heat-sealing pressure is typically 0.1 MPa or higher, preferably 0.5 MPa or higher. Within this range, proper adhesion of the seal is ensured. Furthermore, when using a heated heat-sealing tester with a sealing strip, the upper limit is typically 1.0 MPa or lower, preferably 0.75 MPa or lower. Within this range, thinning of the film at the sealing end is avoided, ensuring sealing strength.
[0095] In addition, to improve the physical properties of this molded body, it is also possible to composite it with a molded body made of a different material (e.g., fiber, filament, rope, fabric, knitted fabric, nonwoven fabric, paper, film, sheet, tube, plate, rod, container, bag, component, foam, etc.). These materials are also preferably biodegradable.
[0096] Preferred embodiments of this disclosure are set forth in the following items, but the invention is not limited to the following items.
[0097] [Project 1]
[0098] A biodegradable laminate comprises, in sequence: a paper substrate (A) layer, a first thermoplastic resin (B) layer with poly(3-hydroxyalkanoate) resin as the main component, and a second thermoplastic resin (C) layer with poly(3-hydroxyalkanoate) resin as the main component.
[0099] The first thermoplastic resin (B) contains a poly(3-hydroxyalkanoate) resin with a weight-average molecular weight of 100,000 or more and less than 350,000, and the second thermoplastic resin (C) contains a poly(3-hydroxyalkanoate) resin with a weight-average molecular weight of 450,000 or more and less than 700,000.
[0100] [Project 2]
[0101] According to the biodegradable laminate described in Project 1, an adhesive resin (D) layer is laminated on the back side of the paper substrate (A) layer on which the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer are laminated, and the weight per unit area of layer (D) is 0.1 g / m². 2 Above and below 5.0 g / m 2 .
[0102] [Project 3]
[0103] The biodegradable laminate according to Project 1 or 2 satisfies all of the following (a) to (d):
[0104] (a) The average thickness (t) of the first thermoplastic resin (B) layer mentioned above B ) is 5μm or larger
[0105] (b) The average thickness (t) of the second thermoplastic resin (C) layer mentioned above. C ) is above 10μm
[0106] (c)t B and t C The sum is less than 100μm
[0107] (d) Using t C Divide by t B The obtained value is 2 or higher.
[0108] [Project 4]
[0109] According to the biodegradable laminate of Project 2 or 3, the adhesive resin (D) comprises at least one resin selected from ester resins, acrylic resins, methacrylic resins, vinyl chloride resins, styrene-acrylic resins, styrene-butadiene resins, styrene-isoprene resins, polycarbonate resins, urea resins, melamine resins, epoxy resins, phenolic resins, carbamate resins, diallyl phthalate resins, and imine resins.
[0110] [Project 5]
[0111] A method for manufacturing a biodegradable laminate, comprising the following steps:
[0112] The process of forming at least one of the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer by extrusion lamination.
[0113] [Project 6]
[0114] A method for manufacturing a biodegradable laminate, comprising the following steps:
[0115] The process of simultaneously forming the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer on the paper substrate (A) layer by co-extrusion lamination.
[0116] [Project 7]
[0117] A method for manufacturing a biodegradable laminate, comprising the following steps:
[0118] The process of forming at least one of the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer by hot lamination.
[0119] [Project 8]
[0120] A method for manufacturing a biodegradable laminate, which is the method for manufacturing a biodegradable laminate as described in item 2 or 4, the method comprising:
[0121] The process of forming the adhesive resin (D) layer by applying an aqueous dispersion or organic solvent solution of adhesive resin (D) onto a paper substrate (A) layer.
[0122] [Project 9]
[0123] A molded body comprising any one of items 1 to 4 of the biodegradable laminate.
[0124] Example
[0125] The present invention will be specifically described below through embodiments, but the present invention is not limited to its technical scope by these embodiments.
[0126] [Manufacturing Example]
[0127] (Preparation method of the application solution)
[0128] Coating Solution 1: An aqueous dispersion of P3HB3HH with a solid content concentration of 50% by weight was obtained according to the method described in International Publication No. 2004 / 041936. At this time, the weight-average molecular weight of P3HB3HH was 620,000. Next, the above aqueous dispersion was kept at 60°C for hydrolysis, thereby obtaining a coating solution of P3HB3HH with a weight-average molecular weight of 230,000.
[0129] Coating solution 2: An aqueous emulsion (aqueous dispersion) containing acrylic resin (Kane Kagi Co., Ltd., "Zemrack" registered trademark) with an average particle size of 50 nm and a solid content of 30 wt% was prepared.
[0130] (Method for manufacturing resin powder with P3HB3HH as the main component)
[0131] The P3HB3HH powder used in the examples and comparative examples was manufactured according to the method described in International Publication No. 2019-142845. Specific formulations are shown below.
[0132] P3HB3HH Powder 1: P3HB3HH powder with a weight average molecular weight of 400,000 and a 3HH content of 15 mol% relative to the total of 3HB and 3HH.
[0133] P3HB3HH powder 2: P3HB3HH powder with a weight average molecular weight of 650,000 and a 3HH content of 15 mol% relative to the total of 3HB and 3HH.
[0134] P3HB3HH powder 3: P3HB3HH powder with a weight average molecular weight of 100,000 and a 3HH content of 15 mol% relative to the total of 3HB and 3HH.
[0135] P3HB3HH powder 4: P3HB3HH powder with a weight average molecular weight of 800,000 and a 3HH content of 15 mol% relative to the total of 3HB and 3HH.
[0136] (Method for manufacturing resin particles with P3HB3HH as the main component)
[0137] P3HB3HH Particles 1: P3HB3HH powder 1 (100 parts by weight) was dry-blended with behenicol (0.5 parts by weight) and pentaerythritol (1.0 part by weight). The mixture was melt-blended using a twin-screw extruder at a set temperature of 150°C and a screw speed of 100 rpm, and extruded in filament form. It was then solidified and cut into granules by passing it through 40°C warm water. The weight-average molecular weight is 340,000.
[0138] P3HB3HH granules 2: P3HB3HH powder 2 (100 parts by weight) was dry-blended with behenicol (0.5 parts by weight) and pentaerythritol (1.0 parts by weight). The mixture was melt-blended using a twin-screw extruder at a set temperature of 150°C and a screw speed of 100 rpm, and extruded in filament form. It was then solidified and cut into granules by passing it through 40°C warm water. The weight-average molecular weight is 620,000.
[0139] P3HB3HH granules 3: Compared to the above P3HB3HH powder 3 (100 parts by weight), dry-blended with beheniamamide (0.5 parts by weight) and pentaerythritol (1.0 parts by weight), the mixture was melt-blended using a twin-screw extruder at a set temperature of 150°C and a screw speed of 100 rpm, and extruded in filament form. It was then solidified and cut into granules by passing it through warm water at 40°C. The weight-average molecular weight is 50,000.
[0140] P3HB3HH granules 4: P3HB3HH powder 4 (100 parts by weight) was dry-blended with behenicol (0.5 parts by weight) and pentaerythritol (1.0 parts by weight). The mixture was melt-blended using a twin-screw extruder at a set temperature of 150°C and a screw speed of 100 rpm, and extruded in filament form. It was then solidified and cut into granules by passing it through 40°C warm water. The weight-average molecular weight is 750,000.
[0141] <Manufacturing of Laminated Composites Based on Extrusion Lamination>
[0142] (Example 1)
[0143] For P3HB3HH granules 1, a single-screw extruder equipped with a T-die was used, and the resin temperature directly below the die was adjusted to 175°C for extrusion, resulting in a 20μm thickness and a unit area weight of 200g / m². 2A laminate (S) with a first thermoplastic resin (B) layer laminated on the surface of a paper substrate (A) was obtained. Next, for P3HB3HH particles 2, a single-screw extruder equipped with a T-die was used, and the resin temperature directly below the die was adjusted to 175°C. The particles were extruded and laminated to the surface of the first thermoplastic resin (B) of the laminate (S) with a thickness of 45 μm, resulting in a biodegradable laminate with a first thermoplastic resin (B) layer and a second thermoplastic resin (C) laminated on the paper substrate (A). The structure of the obtained biodegradable laminate is shown in Table 1.
[0144] (Example 2)
[0145] In the biodegradable laminate obtained in Example 1, the side opposite to the side where the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer are laminated is dried at a weight of 3 g / m² using a bar coater. 2 The coating solution 1 was applied in a specific manner, and then thoroughly dried using a hot air oven to form an adhesive resin (D) layer, resulting in a biodegradable laminate. The composition of the obtained biodegradable laminate is shown in Table 1.
[0146] It should be noted that the unit area weight of the adhesive resin (D) layer was determined in advance using the following method.
[0147] [Method for determining the unit area weight of the adhesive resin (D) layer]
[0148] First, for cutting into 10cm pieces 2 A square-sized paper substrate (A) was subjected to a process where moisture was fully evaporated according to Japanese Industrial Standard JISP8127:2010 (Paper and Paperboard - Batch Moisture Test Method - Dryer-based Method), and the weight of the paper substrate (A) was determined. Next, an aqueous coating containing an adhesive resin (D) was applied to the paper substrate (A), and after the moisture was fully evaporated using the same method, the weight was measured. The weight of the applied adhesive resin (D) and its weight per unit area (g / cm²) were obtained from the difference between the applied adhesive resin (D) and the weight of the coated adhesive resin (D). 2 ).
[0149] (Example 3)
[0150] Application solution 2 was used instead of application solution 1, and otherwise, a biodegradable laminate was obtained in the same manner as described in Example 2. The composition of the obtained biodegradable laminate is shown in Table 1.
[0151] (Example 4)
[0152] The thickness of the second thermoplastic resin (C) layer was adjusted to 70 μm. Otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0153] (Example 5)
[0154] The thickness of the first thermoplastic resin (B) layer was adjusted to 10 μm and the thickness of the second thermoplastic resin (C) layer was adjusted to 20 μm. Otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0155] (Example 6)
[0156] The thickness of the second thermoplastic resin (C) layer was adjusted to 20 μm, and otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0157] (Example 7)
[0158] The fabrication was carried out using a co-extrusion laminator, in which a first thermoplastic resin (B) layer and a second thermoplastic resin (C) layer were simultaneously laminated. Otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0159] (Example 8)
[0160] The first thermoplastic resin (B) layer was laminated in the same manner as described in Example 1, with a unit area weight of 200 g / m². 2 A laminate (S) was obtained on paper. Then, using a hot laminator, a P3HB3HH film manufactured using P3HB3HH particles 2 with a thickness of 45 μm was laminated onto the first thermoplastic resin layer (B) of the laminate (S) at a resin surface temperature of 160°C and a pressure of 0.1 MPa, thereby obtaining a biodegradable laminate. The composition of the obtained biodegradable laminate is shown in Table 1.
[0161] (Comparative Example 1)
[0162] P3HB3HH particles 1 were used as the second thermoplastic resin (C) layer. Otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0163] (Comparative Example 2)
[0164] P3HB3HH particles 2 were used as the first thermoplastic resin (B) layer, and otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0165] (Comparative Example 3)
[0166] P3HB3HH particles 2 were used as the first thermoplastic resin (B) layer, and P3HB3HH particles 1 were used as the second thermoplastic resin (C) layer. Otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1.
[0167] (Comparative Example 4)
[0168] P3HB3HH particles 3 were used instead of P3HB3HH particles 1, and otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0169] (Comparative Example 5)
[0170] P3HB3HH particles 4 were used instead of P3HB3HH particles 2, and otherwise, a biodegradable laminate was obtained in the same manner as described in Example 1. The composition of the obtained biodegradable laminate is shown in Table 1.
[0171] [Evaluation Method]
[0172] The lamination strength, heat seal strength, and flexural strength of the biodegradable laminates obtained in the examples and comparative examples were evaluated, and the results are shown in Table 2. It should be noted that the evaluation was performed using the following methods.
[0173] (Evaluation of lamination strength)
[0174] As an evaluation of lamination strength, the adhesion (peel strength) between the paper substrate (A) and the laminated resin layer was evaluated.
[0175] The lamination strength test was conducted the day after the biodegradable laminate was manufactured. Specifically, a thin cross was cut into the thermoplastic resin surface after extrusion lamination using the blade of a cutting knife. NICHIBAN No. CT-17 tape was firmly adhered to the cut area, and then peeled off by hand to form the end. The end was then cut to a width of 15mm, and the peeled laminate and paper were clamped at 180° angles using jigs for the peel strength test. The test was conducted at a tensile speed of 200mm / min. The peel testing machine used was a Shimadzu Autograph EZ-LX (manufactured by Shimadzu Corporation).
[0176] <Evaluation>
[0177] ○:3.0N / 15mm or more
[0178] △: 2.5N / 15mm or more and less than 3.0N / 15mm
[0179] ×: Less than 2.0N / 15mm
[0180] When the above evaluation result is ○ or △, it can be considered to have sufficient lamination strength.
[0181] (Evaluation of heat-sealing properties)
[0182] A heat-sealing test was conducted the day after the biodegradable laminate was fabricated. Using a heat sealer (TP-701-B, TESTER SANGYO), the side with the thermoplastic resin layer was laminated to the other side (the back of the paper substrate (A), or the adhesive resin (D) layer), and pressed at 0.4 MPa for 5 seconds. The maximum temperature reached on the resin surface during bonding was set to 141°C.
[0183] Cut to a width of 15mm according to JIS standard Z0238, a peel strength test was conducted. The test was performed with a clamping distance of 100mm and a tensile speed of 300mm / min. The peel testing machine used was a Shimadzu Autograph EZ-LX (manufactured by Shimadzu Corporation).
[0184] <Evaluation>
[0185] ◎:3.0N / 15mm or more
[0186] ○: 2.3N / 15mm or more and less than 3.0N / 15mm
[0187] △: 1.5N / 15mm or more and less than 2.3N / 15mm
[0188] ×: Less than 1.5N / 15mm
[0189] When the above evaluation result is ◎, ○ or △, it can be considered that it has sufficient heat-sealing properties for obtaining a good molded body.
[0190] (Evaluation of bending resistance)
[0191] Bending resistance was evaluated the day after the biodegradable laminate was fabricated. Specifically, the laminate was bent at a 90° angle with the second thermoplastic resin (C) layer facing outwards, and the bent portion was observed at 500x magnification using a scanning electron microscope to confirm whether striation-like cracks were formed on the resin surface. Additionally, the bent portion was coated with a 10% concentration of edible red dye and allowed to stand for 1 minute before being wiped with a cloth to confirm whether it stained red.
[0192] <Evaluation Criteria>
[0193] ◎: No streaky cracks were observed, nor was any staining caused by consuming red dye solution.
[0194] ○: There are a few striped cracks, but no staining from edible red dye water was observed.
[0195] △: There are obvious striped cracks, but no staining from edible red dye solution was observed.
[0196] ×: There are striped cracks, and staining with edible red dye water can also be observed. If the above evaluation results are ◎, ○ or △, the bending resistance can be considered good.
[0197]
[0198] [Table 2]
[0199]
[0200] <Results>
[0201] As can be seen from Tables 1 and 2, in each embodiment, a biodegradable laminate with sufficient lamination strength between the paper substrate (A) layer and the first thermoplastic resin (B) layer, mechanical strength capable of withstanding bending processing, and high heat-sealing properties capable of withstanding cup forming was obtained.
[0202] On the other hand, in each comparative example, it is not possible to simultaneously achieve sufficient lamination strength between the paper substrate (A) layer and the first thermoplastic resin (B) layer, mechanical strength to withstand bending processing, and high heat-sealing properties to withstand cup forming.
[0203] Therefore, according to the present invention, a biodegradable laminate having sufficient adhesive strength between the paper substrate (A) layer and the first thermoplastic resin (B) layer, mechanical strength capable of withstanding bending processes, and high heat-sealing properties capable of withstanding cup forming, etc., and a method thereof can be provided.
Claims
1. A biodegradable laminate comprising, in sequence: a paper substrate A layer, a first thermoplastic resin B layer with poly(3-hydroxyalkanoate) resin as the main component, and a second thermoplastic resin C layer with poly(3-hydroxyalkanoate) resin as the main component. The weight-average molecular weight of the poly(3-hydroxyalkanoate) resin contained in the first thermoplastic resin B is 100,000 or more and less than 350,000, and the weight-average molecular weight of the poly(3-hydroxyalkanoate) resin contained in the second thermoplastic resin C is 450,000 or more and less than 700,000.
2. The biodegradable laminate according to claim 1, wherein, An adhesive resin layer D is laminated on the back side of the paper substrate A layer, on the side where the first thermoplastic resin layer B and the second thermoplastic resin layer C are stacked. The unit area weight of the adhesive resin layer D is 0.1 g / m². 2 Above and below 5.0 g / m 2 .
3. The biodegradable laminate according to claim 1 or 2, which satisfies all of the following a~d: a. The average thickness t of the first thermoplastic resin B layer B 5μm and above b. The average thickness t of the second thermoplastic resin C layer C For 10μm and above ct B and t C The sum is less than 100μm d. Using t C Divide by t B The obtained value is 2 or higher.
4. The biodegradable laminate according to claim 2, wherein, The adhesive resin D comprises at least one resin selected from ester resins, acrylic resins, vinyl chloride resins, styrene-butadiene resins, styrene-isoprene resins, urea resins, melamine resins, epoxy resins, phenolic resins, and imine resins.
5. The biodegradable laminate according to claim 1 or 2, wherein, The weight-average molecular weight of the poly(3-hydroxyalkanoate) resin contained in the first thermoplastic resin B is 300,000 or more and less than 350,000.
6. The biodegradable laminate according to claim 1 or 2, wherein, The weight-average molecular weight of the poly(3-hydroxyalkanoate) resin contained in the second thermoplastic resin C is 550,000 or more and less than 700,000.
7. The biodegradable laminate according to claim 1 or 2, wherein, The poly(3-hydroxyalkanoate) resin is selected from at least one of the following: Poly(3-hydroxybutyrate), poly(3-hydroxybutyrate-copoly-3-hydroxyhexanoate), poly(3-hydroxybutyrate-copoly-3-hydroxyvalerate), poly(3-hydroxybutyrate-copoly-4-hydroxybutyrate), poly(3-hydroxybutyrate-copoly-3-hydroxyoctanoate), poly(3-hydroxybutyrate-copoly-3-hydroxyoctadecanoate), poly(3-hydroxybutyrate-copoly-3-hydroxydecanoate), poly(3-hydroxybutyrate-copoly-3-hydroxyvalerate-copoly-3-hydroxyhexanoate).
8. The biodegradable laminate according to claim 4, wherein, The acrylic resin is selected from at least one of methacrylic resins and styrene-acrylic resins.
9. A method for manufacturing a biodegradable laminate, comprising the method of manufacturing the biodegradable laminate of claim 1 or 2, the method comprising: The process of forming at least one of the first thermoplastic resin layer B and the second thermoplastic resin layer C by extrusion lamination.
10. A method for manufacturing a biodegradable laminate, comprising the method of manufacturing the biodegradable laminate of claim 1 or 2, the method comprising: The process of simultaneously forming the first thermoplastic resin (B) layer and the second thermoplastic resin (C) layer on the paper substrate A layer by co-extrusion lamination.
11. A method for manufacturing a biodegradable laminate, comprising the method of manufacturing the biodegradable laminate of claim 1 or 2, the method comprising: The process of forming at least one of the first thermoplastic resin layer B and the second thermoplastic resin layer C by hot lamination.
12. A method for manufacturing a biodegradable laminate, comprising the method of manufacturing the biodegradable laminate of claim 2, the method comprising: The process of forming the adhesive resin D layer by applying an aqueous dispersion or organic solvent solution of the adhesive resin D onto a paper substrate A layer.
13. A molded body comprising the biodegradable laminate of claim 1 or 2.
Citation Information
Patent Citations
Production of laminate
JP1994293113A
Resin composition and sheet
WO2010013483A1
Biodegradable polyester resin composition
WO2013147139A1
Laminate and manufacture thereof
JP1994143521A
Biodegradable resin sheet and method for producing the same
JP2014144553A
